The Effect of Past Experience, Empathy, Efficacy and Social Support on Social Entrepreneurial Intentions: Pengaruh Pengalaman Terdahulu, Empati, Efikasi dan Dukungan Sosial terhadap Niat Wirausaha Sosial - Hamdani, Luthfi (Politeknik Harapan Bangsa Surakarta, 2022)
This study aims to measure the various factors that influence the intention to do social entrepreneurship in the younger generation. Students of the Islamic Business Management study program, UIN Raden Mas Said Surakarta were selected as respondents. This study has four independent variables (previous experience, empathy, self-efficacy and social support) and one dependent variable, namely social entrepreneurship intentions. The quantitative method was chosen as the approach and used a questionnaire as an instrument in collecting data. The population in this study amounted to 2097 people consisting of 4th and 6th semester students in 2022. Multiple linear regression analysis was applied to analyze the collected data. The results of the partial test show that the four independent variables have a significant positive effect on the dependent variable. Furthermore, simultaneously the four variables have a significant effect on social entrepreneurial intentions. The four independent variables in this study were able to explain 33.7% of the variation in entrepreneurial intentions, while the rest (66.3%) were explained by various other factors not included in this study.